PREVENTION OF THE SPREAD OF THE IDEOLOGY OF TERRORISM AMONG YOUTH IN THE KARACHAY-CHERKESS REPUBLIC - M. M. Lyau (Современная наука и инновации, 2022)
In order to ensure national security for the long term in the Russian Federation, tasks to improve measures to identify, prevent, suppress and disclose acts of terrorism and extremism are coming to the fore. Thanks to the joint efforts of federal and regional counter-terrorism actors over the past few years, the level of terrorist threat in the country has been steadily declining.